Complete Dissolution of a Small Gallstone After Three Months of Ursodeoxycholic Acid Therapy: A Case Report - I Wayan Oka Semara Jaya; Ignasius Adi Dharma; I Made Suma Wirawan (Jurnal Sehat Indonesia (JUSINDO), 2026)
Cholelithiasis is a common biliary tract disorder frequently encountered in clinical practice. Laparoscopic cholecystectomy remains the standard treatment for symptomatic gallstones; however, nonsurgical therapy with ursodeoxycholic acid (UDCA) may be considered for selected patients with small, uncomplicated gallstones. We report the case of a 68-year-old woman who presented with right upper quadrant abdominal pain. Abdominal ultrasonography revealed a solitary gallstone measuring 0.58 cm without evidence of cholecystitis. The patient was treated with ursodeoxycholic acid at a dose of 500 mg daily. Follow-up ultrasonography performed after three months of therapy demonstrated complete resolution of the gallstone. This case highlights that UDCA may serve as an effective nonsurgical treatment option for selected patients with cholelithiasis, particularly those with small solitary gallstones without inflammatory findings. Clinicians should consider UDCA as a therapeutic alternative for patients who are unsuitable for surgery or decline operative intervention, with routine ultrasonographic follow-up recommended to assess treatment response.